PENDIDIKAN KONSERVASI UNTUK MEWUJUDKAN SIKAP PEDULI LINGKUNGAN DALAM PROGRAM KAMPUNG IKLIM (PROKLIM) DI DUSUN NGRANCAH DESA NGRANCAH KECAMATAN GRABAG KABUPATEN MAGELANG - Riskiyanto, Riskiyanto; Aji, Ananto; Hariyanto, Hariyanto (Indonesian Journal of Conservation, 2018)
Environmental aspects in the development process are generally less attention, just realized and protested after environmental problems resulted in disasters and the perceived loss of society, as it is being felt at this time that is Global Warming. The purpose of this research is to know (1) the role of villages in conservation activities and village of climate, (2) local wisdom related to conservation, (3) community knowledge related to conservation and village of climate, (4) environmental care attitude owned by society. This research is a descriptive research. The population in this study was the community of Dusun Ngrancah aged 20-69 years, amounting to 481 peoples, with samples taken at random as many as 83 people. Data collection using test instruments, questionnaires, observations, interviews and documentation. Data analysis using descriptive percentage. The results of this study indicate that, (1) the role of villages in activities related to conservation and climate of the village included into the medium category (66, 67%), (2) community rules or values related to conservation have been made into village regulations, Related to conservation and the climate of the village are included in the sufficient category (76.19), (3) the community has knowledge about the conservation and the current village of climate with an average score of 71, (4) the community has a high caring attitude (84) to its environment.